Hypoglycemic and Toxic Effect of Morus mesozygia Leaf Extract on the Liver and Kidneys of Alloxan-Induced Hyperglycemic Wistar Rats - Tirwomwe, Michael; Echoru, Isaac; Maseruka, Richard; Kimanje, Kyobe Ronald; Byarugaba, Wilson (Hindawi, 2019)
Diabetes mellitus (DM) is one of the leading causes of mortality and morbidity in developed and developing countries. DM is characterized by increased levels of glucose that eventually progress to frequent urination, increased thirst, and increased hunger [1]. According to global estimates of diabetes, in 2013, 382 million people had diabetes; this number is however expected to rise to 592 million by 2035. Majority of the people with diabetes live in low- and middle-income countries and these will experience the greatest increase in cases of diabetes over the next 22 years [2]. In Africa alone, about 12.1 million people lived with diabetes mellitus by 2010 [3, 4], and according to research, there will be an expected increment in the prevalence of DM in Asia and Africa by 2030. )is is because of increased urbanization and lifestyle changes that have changed the indigenous diet to a modern diet [5].
Keywords: Hypoglycemic; Morus mesozygia Leaf Extract; Liver and Kidneys; Alloxan-Induced Hyperglycemic Wistar Rats